Positive and negative side effects of androgen abuse. The HAARLEM study: A one-year prospective cohort study in 100 men - Smit, D. L.; Buijs, M. M.; de Hon, O.; den Heijer, M.; de Ronde, W. (Scandinavian Journal of Medicine & Science in Sports, 2021)
An estimated 4-6% of fitness center visitors uses anabolic-androgenic steroids (AAS). Reliable data about adverse reactions of AAS are scarce. The HAARLEM study aimed to provide insight into the positive and negative effects of AAS use. One hundred men (=18 years) who intended to start an AAS cycle on short notice were included for follow-up. Clinic visits took place before (T0), at the end (T1), and three months after the end of the AAS cycle (T2), and one year after the start of the cycle (T3), and comprised a medical history, physical examination, laboratory analysis, and psychological questionnaires. During the follow-up period, four subjects reported a serious adverse event, that is, congestive heart failure, acute pancreatitis, suicidal ideation, and exacerbation of ulcerative colitis. All subjects reported positive side effects during AAS use, mainly increased strength (100%), and every subject reported at least one negative health effect. Most common were fluid retention (56%) and agitation (36%) during the cycle, and decreased libido (58%) after the cycle. Acne and gynecomastia were observed in 28% and 19%. Mean alanine transaminase (ALT) and creatinine increased 18.7 U/l and 4.7 µmol/L, respectively. AAS dose and cycle duration were not associated with the type and severity of side effects. After one-year follow-up (T3), the prevalence of observed effects had returned to baseline. There was no significant change in total scores of questionnaires investigating wellbeing, quality of life, and depression. In conclusion, all subjects experienced positive effects during AAS use. Four subjects experienced a serious adverse event. Other side effects were mostly anticipated, mild, and transient.